The Use of Tungsten in Potentiometry to Detect Pospat Baffer and Urease Enzyme - Victor H Sihombing; Abd Hakim S (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to characterize phosphate buffer and urease enzymes through the absorbance spectrum of UV-Vis and FTIR using tungsten as the indicator electrode. The method used in this research is the biosensor potentiometric method carried out in the Laboratory of the Faculty of Mathematics and Natural Sciences, State University of Medan and the Beacukai Belawan Medan laboratory. The absorbance characterization of electrolyte solutions in various compositions using UV-Vis showed that phosphate buffer solution 0.001 M pH 7.5+KCl 0.001 M + urea 0.001 M+3 drops urease enzyme had the highest absorbance compared to electrolyte solutions with phosphate buffer and urea content. Likewise, the FTIR results showed the same thing where phosphate buffer solution was 0.001 M pH 7.5 + KCl 0.001 M + urea 0.001 M + 3 drops urease enzyme had the highest% T (transmission) pattern of phosphate buffer solution and urea. The urease enzyme in this study functions as a catalyst. Based on UV-Vis and FTIR characterization, it was concluded that the phosphate buffer solution of 0.001 M pH 7.5+KCl 0.001 M + urea 0.001 M + 3 drops of urease enzyme was the best.